2014
DOI: 10.1093/hmg/ddu602
|View full text |Cite
|
Sign up to set email alerts
|

SEPN1, an endoplasmic reticulum-localized selenoprotein linked to skeletal muscle pathology, counteracts hyperoxidation by means of redox-regulating SERCA2 pump activity

Abstract: Selenoprotein N (SEPN1) is a broadly expressed resident protein of the endoplasmic reticulum (ER) whose loss-of-function inexplicably leads to human muscle disease. We found that SEPN1 levels parallel those of endoplamic reticulum oxidoreductin 1 (ERO1), an ER protein thiol oxidase, and that SEPN1's redox activity defends the ER from ERO1-generated peroxides. Moreover, we have defined the redox-regulated interactome of SEPN1 and identified the ER calcium import SERCA2 pump as a redox-partner of SEPN1. SEPN1 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 51 publications
5
134
1
Order By: Relevance
“…In order to characterise the chain of events that can connect a hyperoxidised ER to a hyperactive TGF-beta signalling that does not cause fibrosis, we used a cell system of SEPN1 knock-down (SEPN1 KD) C2C12 myoblasts16 (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to characterise the chain of events that can connect a hyperoxidised ER to a hyperactive TGF-beta signalling that does not cause fibrosis, we used a cell system of SEPN1 knock-down (SEPN1 KD) C2C12 myoblasts16 (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…However, despite its ubiquitous expression, the loss-of-function mutation leads to rare early-onset recessive neuromuscular disorders. It has also been shown that SEPN1 knock-out (KO) mice are particularly sensitive to ER hyperoxidation as we have previously found that the over-expression of ERO1 is sufficient to compromise muscle function in SEPN1 KO but not in wild-type (WT) mice16.…”
mentioning
confidence: 83%
“…SelN can also regulate the calcium level in the SR via enhancing SERCA activity by reducing the luminal H 2 O 2 -oxidized cysteines [41]. This is clearly visible in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Expressed during embryonic development of skeletal muscle and to a lesser extend in adult tissue, SelN is an ER glycoprotein. SelN is involved in ER redox process and calcium homeostasis (98). In addition to this severe disease, other studies associate single nucleotide polymorphisms (SNPs) in selenoprotein genes with increased risk of cancers, notably colon cancer (103,104).…”
Section: --mentioning
confidence: 99%